Analysis Of Employment In The Hospitality Sector And Other Accomodation In The City Of Palangka Raya - Royen Simanjuntak; Rima Harati (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2018)
ABSTRACT The purpose of this study is to determine the role of the hospitality sector and other accommodation on the amount of labor absorbed in the sector. This research uses quantitative method with cross sectional approach. The results showed that: a) Where the number of rooms, room rental prices and number of visits have a positive and significant impact on employment. b) The value of coefficient number of rooms amounted to 0.443 means that if there is an increase of 1% of the number of rooms then the absorption of labor by 0.443%. c) The coefficient value for the room rental price of 0,507 means that if the room rental price increases by 1% causes the increase in the amount of labor by 0.507%. d) Value of visitor number coefficient of 0.279 means if the number of visitors increased by 1% then the employment of 0.279%. The results showed X1, X2, X3 simultaneously have a significant effect on employment in the hospitality sector and other accommodation in Palangkaraya City and T-test results indicate that star hotels and non-star hotels have an influence on visitors to choose hotels.